Capital Structure and Financial Performance of Commercial Banks in Ghana - Deodat E. Adenutsi (Business, Management and Economics - Research Progress Vol. 1, 2024)
This paper investigates the impact of capital structure on the financial performance of commercial banks in Ghana for the period, 2008-2022. The methodology involves a robust analytical framework using econometric models, particularly the Panel Autoregressive Distributed Lag (P-ARDL) regression model enabling a thorough examination of the complex interactions between capital structure and bank performance. Spanning five listed banks over a 15-year period for which consistent data is available, panel-data econometric modelling was used to accommodate individual heterogeneity. The findings reveal a significant long-run positive impact of capital structure on financial performance, suggesting that optimal capital structure can enhance bank performance in the long run. In the short run, capital structure contemporaneously and sluggishly impacts ROA negatively, but with only a weak negative sluggish effect on ROE. The results further highlight the significant long-run detrimental effect of bank size and the robust positive long-run effect of bank growth on the financial performance of banks. The paper recommends a strategic focus on optimising capital structure to enhance the long-run financial performance of Ghanaian commercial banks thereby underscoring the importance of considering internal factors in capital structure decisions. This study contributes to the global discourse on capital structure, offering fresh perspectives from an underdeveloped economic context.